2018
DOI: 10.1088/1361-6528/aa9cc6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of charge trapping and classification of sub-gap states in MoS2 TFT by pulse IV method

Abstract: The threshold voltage instabilities and huge hysteresis of MoS thin film transistors (TFTs) have raised concerns about their practical applicability in next-generation switching devices. These behaviors are associated with charge trapping, which stems from tunneling to the adjacent trap site, interfacial redox reaction and interface and/or bulk trap states. In this report, we present quantitative analysis on the electron charge trapping mechanism of MoS TFT by fast pulse I-V method and the space charge limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…where μ fast is the extracted mobility from the single-pulse measurement. 23,31) Figure 6(b) compares the extracted…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where μ fast is the extracted mobility from the single-pulse measurement. 23,31) Figure 6(b) compares the extracted…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19] Although surface passivation or electrical characterization in vacuum are recommended to minimize the surface trapping effect, pulsed measurements have been proposed as a simple and reliable method to evaluate intrinsic properties of 2D semiconductors. [20][21][22][23] However, limited studies were reported on pulsed I-V study of p-type 2D FETs.…”
Section: Introductionmentioning
confidence: 99%
“…It means that the conduction properties of this structure can flexibly switch between high resistance property and low resistance property. We analyzed the electric transport process in this structure and attribute this switchable effect to the change of Schottky barrier caused by the charge trapping effect [21][22][23][24][25][26]. This work may help develop a new approach for the design of resistance devices and provide the incentive for the development of laser-and pulse-modulated photoelectric devices.…”
Section: Introductionmentioning
confidence: 98%
“…The quality of interface between gate insulator and the GaN cap layer is crucial for the AlGaN/GaN MISHEMTs to achieve excellent and reliable performance. For example, in switching applications it is important to investigate the interface traps as they could degrade device switching properties through the charging and discharging phenomenon [90]. Many characterization techniques have been developed to evaluate the interfacial quality.…”
Section: Interface Quality Characterization Via Ac Conductance Methodsmentioning
confidence: 99%
“…The quality of interface between gate insulator and the semiconductor wafer is crucial for the AlGaN/GaN MISHEMTs to achieve excellent and reliable performance. For example, in switching applications it is important to investigate the interface traps as they could degrade device switching properties through charging and discharging [90]. Although researchers have realized MISHEMTs with h-BN, [91]- [93] no interface properties have so far been reported for VO h-BN on AlGaN/GaN heterostructures.…”
Section: Gan Mishemt Using H-bn 41 Introductionmentioning
confidence: 99%